Encyclopedia: Dworkin - Atip Latipulhayat (PADJADJARAN Jurnal Ilmu Hukum (Journal of Law), 2018)
Ronald Myles Dworkin was born in 1931, in Worcester, Massachusetts. He served as professor of law and philosophy at New York University and professor emeritus at University College London. He has a substantial contribution in the fields of philosophy of law and political philosophy. For his services, he received the Holberg International Memorial Prize in the field of humanity in 2007. Dworkin's most influential view is that law as an act of interpretation. Law should be read as an integration in the sense that the judge should interpret the law consistently / coherently towards the principles of political morality of a society, especially pertaining to the value of justice, fairness, and legality. Dworkin is known as the most persistent critic of Hart's legal positivism. The targets of Dworkin's critic include the thesis of Hart's legal positivism regarding law as a system of rules and the separation between law and morality. DOI: https://doi.org/10.22304/pjih.v5n2.a0